Elevated levels of mitochondrion‐associated autophagy inhibitor LRPPRC are associated with poor prognosis in patients with prostate cancer. Issue 8 (3rd January 2014) - Jiang, Xianhan; Li, Xun; Huang, Hai; Jiang, Funeng; Lin, Zhuoyuan; He, Huichan; Chen, Yanru; Yue, Fei; Zou, Jing; He, Yongzhong; You, Pan; Wang, Wenwei; et al.
Abstract : BACKGROUND: Autophagy has recently been found to play important roles in tumorigenesis and leucine‐rich pentatricopeptide repeat motif‐containing protein (LRPPRC) has been identified as an inhibitor that suppresses autophagy and mitophagy and maintains mitochondrial activity. The authors hypothesized that LRPPRC levels can be used as a biomarker for the diagnosis and prognosis of prostate cancer. METHODS: Immunochemistry analysis was performed to evaluate the levels of LRPPRC in 112 samples collected from patients with prostate adenocarcinoma (PCa) and 38 samples from patients with benign prostatic hyperplasia (BPH) who were enrolled in hospitals in Guangzhou City, China and were followed for 10 years. RESULTS: Significantly higher levels of LRPPRC were found in PCa samples compared with BPH samples. Greater than 75% of patients with PCa demonstrated high levels of LRPPRC whereas only 10% of patients with BPH were found to have similar levels of LRPPRC. The levels of LRPPRC were found to be positively correlated with tumor grade, metastasis, and serum prostate‐specific antigen level, but were negatively correlated with hormone therapy sensitivity after 2 years of surgery and overall survival. The association between high levels of LRPPRC and late‐stage PCa or hormone therapy insensitivity was confirmed in tissue samples collected from prostate‐specific phosphatase and tensin homolog ( PTEN ) ‐/‐ mice or hormone‐dependent and hormone‐independent PCa cell lines. CONCLUSIONS: LRPPRC levels may be used as an independent biomarker for patients with PCa at a late stage with poor prognosis. Cancer 2014;120:1228–1236 . © 2014 American Cancer Society . Abstract : Leucine‐rich pentatricopeptide repeat motif‐containing protein (LRPPRC) is a mitochondrion‐associated autophagy inhibitor that protects mitochondria from degradation. To the authors' knowledge, the current study is the first to demonstrate that high levels of LRPPRC are associated with poor prognosis in patients with late‐stage prostate cancer.